2022
DOI: 10.1097/bsd.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Health Care Resource Utilization of Iatrogenic Spinal Cerebrospinal Fluid Leaks in the United States

Abstract: Study Design: Retrospective cohort study. Objective: We aimed to characterize the treatment patterns and the associated costs in patients with cerebrospinal fluid (CSF) leak after spine procedures in the United States. Background: CSF leak is a common complication after spinal procedures. However, there is a little data regarding the national patterns of treatment choice and the associated health care resource utilization. Methods: We utilized the IBM MarketScan Research databases to retrospectively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Postoperative CSF leaks are common in spine surgery. 1,[8][9][10] Only a very small fraction of these patients have persistent extensive extradural CSF collections requiring specialized spinal imaging such as DSM to pinpoint the exact site of the CSF leak. Similar to postdural puncture CSF leaks with associated extensive extradural CSF collections, where we found that DSM was able to localize the exact location of the CSF leaks in 5 (100%) of 5 patients, 5 this study showed that DSM was able to demonstrate the exact site of the dural breach in 19 (90%) of 21 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative CSF leaks are common in spine surgery. 1,[8][9][10] Only a very small fraction of these patients have persistent extensive extradural CSF collections requiring specialized spinal imaging such as DSM to pinpoint the exact site of the CSF leak. Similar to postdural puncture CSF leaks with associated extensive extradural CSF collections, where we found that DSM was able to localize the exact location of the CSF leaks in 5 (100%) of 5 patients, 5 this study showed that DSM was able to demonstrate the exact site of the dural breach in 19 (90%) of 21 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of postoperative spinal cerebrospinal fluid (CSF) leaks has received relatively scant attention compared with spontaneous spinal CSF leaks although they are by far more common. 1,2 Partly, this can be explained by the fact that generally there is little doubt about the location of the iatrogenic CSF leak. However, in patients with extensive postoperative extradural spinal CSF collections, the exact site of the dural breach is not always clear, and further investigations are necessary to determine the leak site.…”
mentioning
confidence: 99%